2010
DOI: 10.2337/diaclin.28.3.121
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Benefit of Self-Monitoring of Blood Glucose Is Uncertain for Non–Insulin-Treated Patients With Type 2 Diabetes

Abstract: C: Self-monitoring of blood glucose in non-insulin treated patients with type 2 diabetes: a systematic review and meta-analysis. Curr Med Res Opin 25:2903-2913, 2009 SUMMARY Design. A comprehensive systematic review and meta-analysis. Objective. To assess the effect of self-monitoring of blood glucose (SMBG) on A1C in non-insulintreated patients with type 2 diabetes. Subjects. The analysis included 3,270 non-insulin-treated patients with type 2 diabetes in Canada, the United States, Europe, and Asia. In the 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Interestingly, the systematic review by Gerrald et al [ 51 ], found no benefit of telemonitoring in improving HbA1c and reported that HbA1c was unaffected by education aimed at self-management and study follow-up. This was also the case in some of the selected papers for this systematic review that reported no statistically significant benefit of education in improving HbA1c.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the systematic review by Gerrald et al [ 51 ], found no benefit of telemonitoring in improving HbA1c and reported that HbA1c was unaffected by education aimed at self-management and study follow-up. This was also the case in some of the selected papers for this systematic review that reported no statistically significant benefit of education in improving HbA1c.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the participants in our study were under the age of 65 and therefore not covered by the Ontario Drug Plan, which reimburses SMBG expenses. There is mounting evidence that SMBG is not cost-effective and many advocate that the frequency of SMBG for patients with Type 2 DM not treated with insulin should be limited (i.e., 1–2 times per week) [ 12 , 37 ], which can incur a substantial reduction in expenditures [ 17 ]. In response to this evidence, the Canadian Diabetes Association released more specific SMBG guidelines stating that patients who are not treated with insulin, have stable and controlled blood glucose levels, and are not at risk of hypoglycemia would benefit from performing SMBG less than 2 times per week [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unter ärztlicher Supervision sind Patienten dabei angehalten, ihre eigenen Blutzuckerwerte regel mäßig zu erheben und zu protokollieren. Die so erhobenen Daten erlauben es, einen stetigen Krankheitsverlauf sicher zustellen, da auf auffällige Werte zeitgerecht reagiert werden kann [16].…”
Section: Diabetes-selbstmanagement In Der Sekundärpräventionunclassified